Optical Network Monitoring System with Graphical User Interface using Various Properties of Fiber Bragg Gratings - Fadzlina Naim, Nani; Fathiyah Abd Kadir, Nur; Seroja Sarnin, Suzi; Ihsan Mohd Yassin, Ahmad; Yaâ€™acob, Norsuzila; Idris, Azlina; Norsyafizan W. Muhamad, W.; Sarah Supian, Latifah (International Journal of Engineering and Technology, 2019)
This paper presents an automatic and real time domain optical network monitoring system. The system is designed using OptiSystem software to monitor a point-to-multipoint (P2MP) Time Division Multiplexing - Passive Optical Network (TDM-PON). This system is capable to monitor the health of the distribution fibers in P2MP network using Fiber Bragg Gratings (FBGs). Various FBGs with dissimilar bandwidth and reflectivity are placed in the distribution fibers. The FBGs reflection spectra are used as the branch identifiers. Any lost of reflection spectrum shows that there is a fiber failure. A system that will automatically identify the failures has also been developed. The automatic analysis with its graphic user interface (GUI) is developed using MATLAB software. It is found that this automatic monitoring system is able to monitor up to 32 users with monitoring power received of -45 dBm.Â Â